Physics of complex systems - Mryglod, I.M. (Condensed Matter Physics, 2001)
This book was published in 1997 in the series “Proceedings
of the International School of Physics “Enrico
Fermi” and contains the lectures and contributions
presented at the CXXXIV Course of Enrico Fermi
School held 9–19 July 1996 in Varenna on Lake Como,
Italy. The editors and the directors of the Course
were F.Mallamace and H.E.Stanley. The Course focuses
on a “state-of-the-art” level of modern problems
in the physics of complex systems and provides both
an overview of the field and a detailed examination of
the main topics within the field that are currently of
greatest interest to researchers.